Analisis Faktor yang Mempengaruhi Inovasi Layanan dan Internasionalisasi terhadap Profitabilitas UMKM di Indonesia - Sahara, Putri; Saputra, Suyono (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Abstract This study aims to analyze the factors influencing service innovation, internationalization, and profitability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Specifically, it examines the role of entrepreneurial orientation dimensions—innovativeness, proactiveness, and risk-taking—as well as human capital in fostering internationalization and service innovation. The research employs a quantitative approach using Structural Equation Modeling (SEM) with the SmartPLS software, analyzing data collected from 140 MSMEs engaged in international activities. The findings reveal that risk-taking and skill & know-how have a significant positive influence on internationalization, while innovativeness and proactiveness show significant negative effects. Surprisingly, service innovation has a negative impact on profitability, indicating that the costs associated with implementing service innovation may outweigh short-term benefits. Furthermore, creativity, proactiveness, and human capital do not significantly influence service innovation, suggesting that additional resources, technology, and strategic planning are needed to strengthen service innovation efforts.These results emphasize the importance of risk management, strategic planning, and skill development in supporting MSME internationalization and innovation. Policymakers and stakeholders must provide financial incentives, technological support, and capacity-building programs to enhance MSME competitiveness in global markets.